Eucalyptus woodlot adoption and its determinants in the Mecha District, Northern Ethiopia - Alemayehu, Asabeneh; Melka, Yoseph; Eshete, Abeje (Frontiers in Forests and Global Change, 2023)
The land area under Eucalyptus plantations has now significantly increased among Ethiopian smallholder farmers whereby Eucalyptus is grown on their farms in the form of a woodlot primarily for income generation. Despite its widespread adoption, studies and systematic documentation on its adoption and economic impact are inadequate to inform evidence-based policy development. The purpose of this study was to investigate the variables influencing the adoption of Eucalyptus woodlot in Mecha District, northern Ethiopia. A multistage sampling method was used to sample 186 respondent households from three villages namely Enashenifalen, Addisameba, and Rim in the district. Primary data was gathered through key informants (thirteen), in-depth interviews, focus group discussions (three), and direct observations, which were complemented by data from secondary sources obtained from published and unpublished documents. A double-hurdle econometric model was used to identify factors influencing households' adoption decisions and adoption intensity of Eucalyptus woodlot. The findings indicate that household adoption decisions are significantly influenced by the number of parcels of land, off-farm work engagement, credit availability, and farmers' perceptions of woodlot production. Family size (negatively), land holding size, number of parcels of land, market access, the adjacent farm, and farmers' perceptions of Eucalyptus woodlot production all significantly influenced the adoption intensity of Eucalyptus woodlots. Furthermore, the major constraints were a lack of support and training, a lack of land segregation, and limited technologies. Providing support and training, alternative options for farmers, cluster planting, technology adoption, developing and implementing Eucalyptus policies, and enforcing rules and regulations are all areas that need to be addressed to improve the livelihood of the community.